Analisa Pengaruh Penerapan Manajemen Kualitas Dengan Mbnqa Kriteria Terhadap Kinerja Bisnis Pada Rumah Sakit Islam Jemursari Surabaya - Arief Sabda Pietra Mukti Sutikno; Febriana Wurjaningrum (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2015)
Today, high population growth coupled with the needs of the product or service quality healthcare. One practice in improving quality is through the implementation of Total Quality Management or TQM. One of the efforts in the implementation of TQM can be done with criteria MBNQA consisting of leadership, strategic planning, customer focus, pekuruan, analysis, and knowledge management, workforce focus, process management, and business results. RSI Jemursari Surabaya as one of the hospitals of foundation hospitals islam Islam Surabaya (Yarsis) has implemented MBNQA in its business operations. This study examines the relationship between TQM implementation through MBNQA on business performance criteria of Islamic Hospital Jemursari. Data were analyzed using path analysis using Partial Least Square method with the help of software SmartPLS. From the research results obtained by the t-statistic for the criteria of customer focus 6.153 ; management process by 5.451; 5.168 leadership; strategic planning 4.314; and 2,628 business results. While the measurement, analysis, and knowledge management did not prove significant influence and adversely affect the value of the path coefficient of -0.014 with 0.288 t and the focus of labor is not proved significant with path coefficient value of 0,020 with 0,349 t.